Book Review: EU Trade Law, Rafael Leal-Arcas (Edward Elgar Publishing, 2019) - Ondrej Svoboda (Croatian Yearbook of European Law and Policy, 2020)
Book Review: EU Trade Law, by Rafael Leal-Arcas (Edward Elgar Publishing, 2019, ISBN 9781788977401), 352 pp, £90,00.